Análise da condutividade térmica da gelatina com variação de umidade - aplicação ao processo de secagem - Sousa, Luiza Helena Costa Dutra (1996)
Gelatin is a very important product for industries due to its coagulativy, protective and adhesive properties. This work deals with the experimental determination of thermal conductivity of gelatin, which is an important parameter for its drying process. The main motivation for carrying out this work was the industrial interest in developing a better quality gelatin product. It was verified a lack of experimental data concerning the thermal conductivity of industrial gelatin in function of moisture. This data are quite important for designing dryers. Parallel plates and linear probes were used under conditions of permanent and transient regimes respectively, for determining the experimental gelatin thermal conductivity. The linear probe was used as a comparison basis for a large and an small parallel plates. Better results were obtained with the smaller area plates, which are less prone to thermal inertia. The industrial gelatin used was provided by Leiner Gelatin of Brazil Ltd, which presented in cylinders shapes having around 3,0 mm diameter and 300,0 mm length. This gelatin material was transformed in smaller particles than its original size, for a perfect accommodation of an homogeneous and compact sample in the measurement cell. Experimental results obtained with parallel plates have demonstrated that the thermal conductivity has a linear dependency of the moisture percentage. Thermal conductivity values varied from 0.128 up to 0.467 Kcal/(h.m.ºC) for moisture values varying from 10% up to 75% respectively. Results of thermal conductivity obtained with the parallel plates when compared to those obtained by using linear probes, demonstrates that the use of parallel plates, specially the small plates, is an efficient method for determining thermal conductivity.